Coping strategies of student assistants in UPV Miagao. - Garilva, Noralyn G.
The researcher attempted to know the efficacious coping strategies perceived by the student assistants of the University of the Philippines in the Visayas for the second semester of the academic year 1995-96 were also the researcher wanted to know whether there is a significant difference on the perceived efficacy of the coping strategies of the student assistants. The researcher pre-surveyed the coping strategies that student assistants employed. From the given coping strategies, the number of categories were established. This study considered only one intervening variable which is gender. The researcher used simple random sampling for the pretest availing the twenty student assistants of the West Visayas State University. For the final test, twenty-five randomly sampled student assistants of the University of the Philippines in the Visayas were taken as respondents. They represent the fifty percent of the total population. Perceived efficacy of the coping strategies were assessed using the 100-item questionnarie containing specific coping strategies. Five-point scale was utilized in order to rate the perceived coping efficacy. Each of the item was pretested using the test of mean difference. Thirty reliable items appeared. Under the problem-focused coping: nine items from the acceptance of responsibilities, four from flexibility, one from self discipline and one from set-up priorities. Under the emotion-focused coping: nine from enjoyment of work and study, one from the use of divine support. And under both problem and emotion-focused coping: five items from the use of others' support. Finally, it was determined that given the categories that were established in the study, the following are considered efficacious coping strategies based on student assistants' perception presented in order: self-discipline, set-up priorities and follow them, use of divine support, enjoyment of work and studies, acceptance of responsibilities, flexibility and use of support from others. These results were obtained by the use of the Perceived Efficacy Index. Mann-Whitney U-Test was utilized in order to test the difference between male and female student assistants which yielded a result stating that there is no significant difference between gender based on the perceived efficacy of the coping strategies of the student assistants. The Test of Difference was computed for each category of coping strategies.